Novel Volumetric and Surface-Based Magnetic Resonance Indices of the Aging Brain – Does Male and Female Brain Age in the Same Way? - Podgórski, Przemysław; Bladowska, Joanna; Sasiadek, Marek; Zimny, Anna (Frontiers in Neurology, 2021)
Introduction: Novel postprocessing methods allow not only for assessment of brain volumetry or cortical thickness based on magnetic resonance imaging (MRI) but also for more detailed analysis of cortical shape and complexity using parameters such as: sulcus depth, gyrification index or fractal dimension. The aim of this study was to analyze changes in brain volumetry and other cortical indices during aging in men and women. Material and methods: Material consisted of 697 healthy volunteers (aged 38-80 years, M/F 264/443) who underwent brain MRI using 1.5 T scanner. Voxel-based volumetry of total gray matter (GM), white matter (WM) and cerebrospinal fluid (CSF) was performed followed by assessment of cortical parameters (cortical thickness (CT), sulcus depth (SD), gyrification index (GI) and fractal dimension (FD)) in 150 atlas locations using surface- based morphometry with a region-based approach. All parameters were compared among seven age groups (grouped every 5 years) separately for men and women. Additionally percentile curves for men and women were provided for total volumes of GM, WM and CSF. Results: In men and women decrease in GM and WM volumes and increase in CSF volume seem to progress slowly since the age of 45. In men significant GM and WM loss as well as CSF increase start above 55 years of age while in women significant GM loss starts above 50 and significant WM loss as well as CSF increase above 60. CT was found to significantly decrease with aging in 39% of locations in women and in 36% of locations in men, SD was found to increase in 13.5% of locations in women and in 1.3% of locations in men, GI was decreased in 3.4% of locations in women and in 2.0% of locations in men and FD was changed in 2.7% of locations in women compared to 2.0% in men. Conclusions: Male and female brains start aging at the similar age of 45. Compared to men, in women the cortex is affected earlier and in the more complex pattern regarding not only cortical loss but also other alterations within cortical shape, with relatively longer sparing of WM volume.